Performance of concrete using aggregate laterite as aggregate replacement - Muhamad Hafizzan, Muhamad Zaidi (2012)
The study on the alternative materials for use as coarse aggregate in concrete mixed should be done in order to prepare on the shortage of granite someday and to know the performance of the alternative material in concrete. Aggregates are the most mined material in the world. The extraction and use of aggregates from natural resources has been questioned at an international level because of the depletion of quality primary aggregates. This can be overcome if other type of aggregate such as laterite aggregate can be as a solution. The main objective of this researcher is to determine specific gravity and water absorption of aggregate, its compression strength and splitting tensile strength. The result is getting by doing in laboratory testing. A total of four batches of concrete are produced, in which one of it is normal concrete and the other is concrete with difference percentage of laterite aggregate which is 15%, 25% and 35% of normal aggregate. In this study, the mixed of concrete used in this research is for grade 35N/mm2 and the water/cement ratio is 0.57. For specific gravity and water absorption, two samples for each aggregate are used. In compression testing, about 36 cubes of concrete with 150mm square in dimension are used for 7, 14, and 28 days curing. 12 cylindrical sample of concrete are used for splitting tensile test at age 28 days. The results show that the strength of laterite concrete for sample B, C, D are 25.643MPa, 29.130MPa, 26.553MPa respectively for age 28 days. It also proves that aggregate granite of higher in specific gravity than laterite aggregate with granite have 2.77 and 2.56 for laterite aggregate. Granite aggregate have lower water absorption than laterite aggregate with 0.70% and 10.66% respectively. In tensile strength, sample A, B, C and Dare 2.13 lMPa, 2.460MPa, 2.113MPa and 2.313MPa respectively.